The Decline of Romanticism in Mary Shelly’s Frankenstein, Mark Twain’s The Adventures of Huckleberry Finn, and Edgar Allen Poe’s The Black Cat. - Alkouri, Ahmad Mohd (Advances in Social Sciences Research Journal, 2020)
This paper explores some gaps in the romanticism era using well-known authors. The paper aims to explore the decline of romantic elements in Mary Shelly’s Frankenstein, Mark Twain’s The Adventures of Huckleberry Finn, and Edgar Allen Poe’s The Black Cat. It provides some hints to foreground further studies on those writers using the approach of critical analysis to romantic works. In fact, this paper could be considered partially as a notes review to comprehend how those writers could be the cause of declining the romantic age and begin new different perspectives using their selected compositions. Although they are considered romantic authors, the paper shows somehow they are different from others. The conclusion draws the gaps in portraying the elements of romanticism.